Starch Composition and Glycemic Load of Teo Tuber Flour (Tacca leontopetaloides) Using a Male Rat (Rattus norvegicus) Animal Model - Vrilianika Vrilianika; Margaretha Solang; Muhammad Isra; Djuna Lamondo; Zuliyanto Zakaria (Biology, Medicine, & Natural Product Chemistry, 2026)
Teo tuber flour (Tacca leontopetaloides) is a local carbohydrate source with potential to be developed as a functional food. However, information about its starch composition and glycemic load is still limited, even though these two parameters are important in determining blood glucose response after consumption as well as the carbohydrate quality of a food. This study aims to determine the amylose and amylopectin content of teo tuber flour and evaluate its glycemic load using male white rats (Rattus norvegicus). The study used a descriptive method with a quantitative approach and a laboratory experimental design. Analysis of amylose and amylopectin content was done using spectrophotometry with the DNS method and an amylose standard curve. Glycemic load was determined by measuring the rats’ blood glucose response after giving them teo tuber flour porridge and pure glucose, then calculated using the Incremental Area Under the Curve (iAUC) method. Research results show that teo yam flour contains 15.727% amylose and 64.389% amylopectin, meaning its starch composition is dominated by amylopectin. Rats fed with teo yam flour porridge showed lower and more stable blood glucose responses compared to rats given pure glucose. The glycemic load value of teo yam flour is 17, which falls into the medium category. These findings suggest that teo yam flour has the potential to be developed as a functional food that can help maintain stable blood glucose levels. Further research is needed to explore starch modification techniques that can reduce glycemic response and enhance its health benefits.